2020
DOI: 10.3390/ijms21020499
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Chitosan Conjugates: Current Synthetic Strategies and Potential Applications

Abstract: As a natural polysaccharide, chitosan possesses good biocompatibility, biodegradability and biosafety. Its hydroxyl and amino groups make it an ideal carrier material in the construction of polymer-drug conjugates. In recent years, various synthetic strategies have been used to couple chitosan with active substances to obtain conjugates with diverse structures and unique functions. In particular, chitosan conjugates with antimicrobial activity have shown great application prospects in the fields of medicine, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 125 publications
0
74
0
Order By: Relevance
“…Chitosan, a polysaccharide derived from the partial deacetylation of chitin, is a cationic linear biopolymer [ 8 , 9 ]. It has been widely considered as one of the safest biomaterials for various biomedical applications [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, a polysaccharide derived from the partial deacetylation of chitin, is a cationic linear biopolymer [ 8 , 9 ]. It has been widely considered as one of the safest biomaterials for various biomedical applications [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that chitosan possesses strong antimicrobial activity against a wide range of microorganisms, such as fungi (molds and yeasts), Gram-positive and Gram-negative bacteria [ 8 , 11 ]. Some studies have reported that chitosan is considered to possess stronger antibacterial activity against Gram-negative bacteria compared with Gram-positive bacteria, although there is some controversy regarding this fact as the opposite has also been stated by other authors [ 49 , 50 , 51 ].…”
Section: Chitosanmentioning
confidence: 99%
“…Among most studies, it has been reported that chitosan also has antimicrobial and antioxidant activities which promote its use in the fields of food protection and the pharmaceutical industry in particular [ 7 ]. In addition to effectively enhancing the shelf life of food ingredients, preventing oxidative damages and inhibiting food-borne pathogens development, it can also increase drugs’ solubility and retention in the site where they are applied [ 2 , 8 , 9 , 10 , 11 ]. However, chitosan has certain limitations and not all chitosans display optimal properties, and research has shown that chitosan with a poor water-solubility at neutral or basic pH and therefore may have limited applications [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For more information on this aspect of the field, the reader is referred to the following texts. [34][35][36] In this Review, an overview of biofilm formation will be given, including a brief description of biofilm structure and function, which gives rise to their resistance and tolerance towards conventional antibiotic treatments. This will be followed by a review of strategies that exploit antibiofilm peptides and proteins, as well as their synthetic polymer counterparts, and nanoparticles thereof.…”
Section: Introductionmentioning
confidence: 99%